2004
DOI: 10.1111/j.1365-2559.2004.01968.x
|View full text |Cite
|
Sign up to set email alerts
|

Rare expression of KIT (CD117) in lymphomas: a tissue microarray study of 1166 cases

Abstract: KIT expression is a very rare event in NHL and virtually absent in HL. In the few positive cases, the aberrant expression is not caused by a mutation in the 'hot-spots' of the kit gene, indicating that treatment of these tumours with Imatinib may be ineffective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…Other single genes affected by copy number alterations in this study that warrant further analysis are KIT, FHIT, PEX14, and PTPRD, which have been previously linked to both hematological malignancies and solid tumors (Gavva et al, 2002;Chen et al, 2004;Kameoka et al, 2004;Zimpfer et al, 2004;Zhao et al, 2006;Purdie et al, 2007). Of particular interest, our SNP results show in one case (no.…”
Section: Discussionmentioning
confidence: 76%
“…Other single genes affected by copy number alterations in this study that warrant further analysis are KIT, FHIT, PEX14, and PTPRD, which have been previously linked to both hematological malignancies and solid tumors (Gavva et al, 2002;Chen et al, 2004;Kameoka et al, 2004;Zimpfer et al, 2004;Zhao et al, 2006;Purdie et al, 2007). Of particular interest, our SNP results show in one case (no.…”
Section: Discussionmentioning
confidence: 76%
“…The soundness of our analysis, the multiple previous validations of the TMA used [29][30][31][32][33][34][35] as well as the κ-values for the comparison of results from conventional lymphoma slides and TMA guarantee the reliability of the data obtained. We clearly demonstrated that the FOXP3 + cell density varies between different lymphoma types and that do lymphoma-infiltrating FOXP3 + cells may represent important lymphoma/host microenvironment-modulators, since increased amounts of these cells can positively influence survival in FL, GC-like DLBCL and cHL.…”
Section: Discussionmentioning
confidence: 99%
“…The tissue microarray (TMA) were constructed and validated as described elsewhere [29][30][31][32][33][34][35] (see Supplementary Data). In cases of FL, neoplastic GC were sampled for arraying.…”
Section: Tissue Microarray Constructionmentioning
confidence: 99%
“…The construction of the TMA was approved by the institutional review boards of the participating centres at the time of case submission and cases have been irreversibly anonymized, which met local legal and ethical requirements for its use in the present study. The arrays have been previously extensively characterized [29][30][31]. DLBCL cases were classified as phenotypic GCB-like, non-GCB-DLBCL and unclassifiable by applying the Hans' algorithm [32].…”
Section: Immunohistochemistrymentioning
confidence: 99%